Project planning tool - Alias, Hafiza (2005)
Doing planning in the early stage of a project is critical. This is because a project plan establishes and maintains a plan that defines the project activities. This in tum will provide a project manager useful information to make decisions to achieve project goals. The Malay Language Project Planning Tool described in this thesis takes a further step to help project managers do their project planning by automating the process of establishing project budget, producing a schedule, identifying potential project risks, managing project data, determining the stakeholders and resources needed, and required skill to have in the project. Developed usmg C# programmmg language on Microsoft's .NET platform and supported by Microsoft SQL Server 2000 for its database, this system is built for a client-server environment and is meant to be used in an organization that uses Malay Language as its medium and where information can be shared by authorized users of the system.